The Effect of the "Marbel Reading" Educational Game Application on the Beginning Reading Ability of Students in Islamic Elementary School - Clarinza Fiorentine Damayanti; Kemil Wachidah (Adabiyah: Jurnal Pendidikan Islam, 2023)
Marbel Reading Educational Game Application is an application that aims to help its users learn while playing. This study aims to determine how the influence of the "Marbel Reading" Game Application on the Beginning Reading Ability of Grade 1 Students. This type of research is a quantitative research with a pre-experimental research method One Group Pretest-Postest using all first grade students of SD Islam Nurul Hikam Banjarbendo. consisting of 20 students. Sampling with non-probability techniques. The research instrument used was in the form of multiple choice test questions regarding early reading skills. Data analysis using normality test, t-test, and eta square test. Based on the results of the pretest-posttest get an average value of 31.80. The minimum score is 55.7. The maximum score is 87.5, the statistical standard deviation is 12,547, and the standard deviation error is 2.806. The results of the paired sample t-test concluded that the value was 0.000, meaning the value of sig <0.05, then there was an effect of variable X on variable Y. Then the eta-square test concluded that the value was 0.244, which means the value of sig t 0.14 means that there is a big influence. It is hoped that the results of this study can have a positive impact on its users. The use of the Marbel Reading application is suitable for low grade students to help maximize their early reading skills.